Manajemen Layanan Khusus Unit Kesehatan Sekolah Di SMK Negeri 5 Jember - Juwita Nur Aisyah; Ririn Wahyuni; Abdul Aziz; Rofiq Hidayat (Jurnal Manajemen Riset Inovasi, 2024)
The School Health Unit / UKS is an integral element in the management of special services in the field of school health. The management of this special service basically aims to support the learning process and meet the specific needs of students in the school environment. This research aims to determine how is the management of the uks at State Vocational School 5 Jember. This research uses qualitative methods and a field research approach. Data collected through interview techniques, observation and documentation. The results of this research can provide guidance to schools to improve the quality and efficiency of health services, as well as promote healthy lifestyles among students. Apart from that, this research also provides a valuable contribution to the development of education and health policies at local and national levels. The benefits of this research have a major impact in improving students’ welfare and health. Through this research, effective efforts can also be identified in ensuring the provision of optimal health services in the school environment